Enteral Vancomycin to Eliminate MRSA Carriership of the Digestive Tract in Critically Ill Patients - Sophie H. Buitinck; Matty Koopmans; Rogier M. Determann; Rogier R. Jansen; Peter H. J. van der Voort (MDPI AG, 2022)
Background: Carriership with methicillin resistant Staphylococcus aureus (MRSA) is a risk for the development of secondary infections in critically ill patients. Previous studies suggest that enteral vancomycin is able to eliminate enteral carriership with MRSA. Data on individual effects of this treatment are lacking. Methods: Retrospective analysis of a database containing 15 year data of consecutive patients from a mixed medical-(cardio)surgical 18 bedded intensive care unit was conducted. All consecutive critically ill patients with enteral MRSA carriership detected in throat and/or rectal samples were collected. We analyzed those with follow-up cultures to determine the success rate of enteral vancomycin. Topical application of 2% vancomycin in a sticky oral paste was performed combined with a vancomycin solution of 500 mg four times daily in the nasogastric tube. This treatment was added to a regimen of selective digestive tract decontamination (SDD) to prevent ICU acquired infection. Results: Thirteen patients were included. The mean age was 65 years and the median APACHE II score was 21. MRSA was present in the throat in 8 patients and in both throat and rectum in 5 patients. In all patients MRSA was successfully eliminated from both throat and rectum, which took 2-11 days with a median duration until decontamination of 4 days. Secondary infections with MRSA did not occur. Conclusions: Topical treatment with vancomycin in a 2% sticky oral paste four times daily in the nasogastric tube was effective in all patients in the elimination of MRSA and prevented secondary MRSA infections.